2019
DOI: 10.3892/mmr.2019.10303
|View full text |Cite
|
Sign up to set email alerts
|

Novel de novo frameshift variant in the ASXL3 gene in a child with microcephaly and global developmental delay

Abstract: De novo sequence variants, including truncating and splicing variants, in the additional sex-combs like 3 gene ( ASXL3 ) have been described as the cause of Bainbridge-Ropers syndrome (BRS). This pathology is characterized by delayed psychomotor development, severe intellectual disability, growth delay, hypotonia and facial dimorphism. The present study reports a case of a girl (born in 2013) with severe global developmental delay, central hypotonia, microcephaly and poor spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
(69 reference statements)
0
10
0
Order By: Relevance
“…Recent studies showed that WES/WGS can be applied for simultaneous detection and characterization of both CNVs and single-nucleotide variants, which could reduce the number of analyses to one complex test to reach the diagnosis [45]. In our pilot study using targeted NGS with commercially available gene panel we identified pathogenic sequence variants in some patients with negative array-CGH assay and confirm the diagnosis on the molecular level [46].…”
Section: Discussionmentioning
confidence: 84%
“…Recent studies showed that WES/WGS can be applied for simultaneous detection and characterization of both CNVs and single-nucleotide variants, which could reduce the number of analyses to one complex test to reach the diagnosis [45]. In our pilot study using targeted NGS with commercially available gene panel we identified pathogenic sequence variants in some patients with negative array-CGH assay and confirm the diagnosis on the molecular level [46].…”
Section: Discussionmentioning
confidence: 84%
“…In addition to the spice site mutation, variant c.3106C > T (p.Arg1036*) was detected in ve patients and c.4330C > T (p.Arg1444*) was detected in three patients, which suggested they are likely mutational hotspots. The prediction that phenotype severity decreases as the variants occur further away from the 5'-end of exon 11 and towards the 3'-end needs to be further con rmed [19]. More patients should be collected to study the genotype-phenotype correlation in this severe atypical neurodevelopmental disorder.…”
Section: Discussionmentioning
confidence: 98%
“…BRPS was rst described in 2013, in four patients with ASXL3 de novo mutations. To date, 54 patients with a wide age range from 4 months to 47 years were reported [1,2,5,[11][12][13][14][15][16][17][18][19][20][22][23][24][25][26][27][28][29][30]. Mutation spectrum of ASXL3 and the number of patients were listed in Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously made several contributions to the literature with publication of three papers delineating the phenotype of ASXL3 ‐related syndrome (Balasubramanian et al, 2017; Myers et al, 2018; Schirwani et al, 2020). So far, clinical details from a total of 45 patients with ASXL3 ‐related syndrome have been reported in literature (Bainbridge et al, 2013; Balasubramanian et al, 2017; Contreras‐Capetillo et al, 2018; Dad et al, 2017; Dinwiddie et al, 2013; Hori et al, 2016; Koboldt et al, 2018; Kuechler et al, 2017; Myers et al, 2018; Neeta Lakhani et al, 2017; Qiao et al, 2019; Schirwani et al, 2020; Srivastava et al, 2016; Verhoeven et al, 2018; Wayhelova et al, 2019). Clinically, ASXL3 ‐related syndrome, also known as Bainbridge–Ropers syndrome (MIM# 615485), is characterized by a variable degree of intellectual disability (ID), developmental delay (DD) with absent or very limited speech development, hypotonia, feeding difficulties, behavioral problems, and characteristic craniofacial features.…”
Section: Introductionmentioning
confidence: 99%